Chronic Constipation and Its Complications: An Interesting Finding to an Otherwise Commonplace Problem. (12th May 2016) - Cheng, Michelle; Ghahremani, Shahnaz; Roth, Antoinette; Chawla, Soni C.
Background . Fecalomas are hard dense masses separate from surrounding fecal material or bowel contents. This case report intends to provide a brief review of the literature and differential diagnosis for a pelvic mass in a pediatric patient. Case Presentation . The patient is a 5-year-old male presenting with worsening constipation and stool leakage over several months, found to have a rare calcified pelvic mass on abdominal X-ray consistent with a fecaloma. Conclusion . Fecalomas should be considered on the differential diagnosis of pediatric patients who present with chronic constipation and a calcified pelvic mass.